Iowa RBA, December 29, 1997 - Fuller, Charleset al; Iowa Ornithologists' Unionet al (1997)
Email of the Iowa RBA update for December 29, 1997. Highlights of the update include sightings of a Ross's Gull, a Prairie Falcon, Common Redpolls, White-winged Crossbills, and several additional species of Gulls. Also included are handwritten notes for the next week's update with sightings of a Ruby-crowned Kinglet, Snowy Owls, and Northern Saw-whet Owls. Epson - sheet feed/flatbed